Collateral damage according to the rules of international humanitarian law a study of the Amriya shelter crime as an example of American folklore that violated the laws of war - Al-Taie, Haider (Journal of Legal Sciences, 2025)
The rules of international humanitarian law aim to achieve a kind of balance based on the implementation of the principle of proportionality between military necessity, with the advantage it achieves that contributes to weakening the capabilities of the enemy in preparation for its subjugation on the one hand, and human ethics, the protection of which constitutes the goal of legal rules. Armed conflicts witness the exposure of civilians to untold harms on the part of the attacker. It is “collateral damage” that does not lead to his responsibility for it, as it is acceptable according to the rules of international humanitarian law. However, this proposal is based on a wrong idea resulting from broad interpretations and justifications of military necessity at the expense of the protection established as an asset for the protected groups This preliminary study sheds light on a crime committed by the international coalition led by the United States of America in 1991, when it targeted a civilian shelter located in the Al-Amiriyah area, west of the Iraqi capital, Baghdad, where hundreds of civilians, women and children, were sheltering. The American attack led to the killing of all of them, which constituted another crime. A silent crime committed by the United States forces against civilians in Iraq We have studied the above topic through three basic paragraphs, where we explained the legal concept of collateral damage in accordance with international humanitarian law, then we explained the problem of the balance between the principles of humanity and military necessity in cases where some form of collateral damage occurs, and finally we clarified the treatment of these principles according to the events that led to the bombing. Al-Amiriyah shelter according to the American point of view and the response to it from a legal perspective